المساوقة التوافقية بين أنظمة البناء ومعايير العمارة الخضراء نحو نظام بناء أخضر - بدر, رنا (Latakia University Journal -Engineering Sciences Series, 2018)
استطاعت العمارة الخضراء أن تكوّن وتكون تياراً وتوّجهاً معمارياً تبوأ خلال فترة قصيرة نسبياً مكانة مهمة في عالم تقنيات العمارة الحديثة،عبر صياغة واعتماد العديد من الأنظمة ( BAREEAM-HQE-LEED- GREEN STAR .....الخ) ذات نظام الدرجات والتي تنافست العديد من أبنية العالم السكنية منها والتجارية والإدارية و..الخ وفي مختلف الدول على تحقيقها لنيل شهادة بناء أخضر. ولكن هل كان هذا البناء بتحقيقه لتلك الدرجات أخضراً حقاً؟ أم أقل خضرة؟ أم أصفراً؟ أم حتى أكثر اصفراراً؟ وهل كان محققاً للبعد الإنساني في مكوناته الأساسية؟ أم أنه تجاهله على حساب تحقيق التكلفة اللاحدية والمنفعة المكافئة لها والواجب تحقيقها ؟وعليه سيقوم البحث على إيجاد تساوق توافقي بين أنظمة البناء (والتي تحمل بمضمونها البعد الإنساني للمنتج السكني) بمتغيراتها المقاسة على نماذج سكنية نموذجية في مدينة اللاذقية، وبين المتغيرات المستخدمة في نظام LEED بهدف التوصل إلى صياغة نظام بناء أخضر لمدينة اللاذقية يمكن بتطبيقه واعتماده ردم الفجوة بين تقنيات ومعايير العمارة الخضراء بمعناها الإجرائي والمجرد وبين المنتج السكني بأبعاده الإنسانية الواجب تحقيقها في أي توّجه معماري بما يضمن الاستمرارية والمضمون الايجابي لمنتجه المعماري.Through a short relatively period green architecture was able to establish and to be an important architectural trend among the recent architecture techniques’ world , by forming and adopting a number of grades type’s systems (green star,leed,hqe, bareem…..etc) whereas a lot of residential , commercial and administrative buildings compete to achieve it towards having a green building certificate.But was this building by having those dependant grades really green?or less green? Or yellow? Or more yellow? and was it human in its basic components? or it ignored that on account of achieving the unlimited cost and its equal benefit which must be achieved?Upon to that the research will work to find that homogeneous symmetry between building codes ( which take care of human dimension of the residential product)with its measured variables on a typical residential types in latakia city and the used LEED variables to reach to a green building code for latakia city which by implementing and depending it can fill the gap between the criteria and techniques of green architecture with its mere implemented meaning and the residential product with its human dimension which must be achieved in any architectural trend to ensure the continuity and positive meaning of its architectural product.